(untitled) (Research, Society and Development, 2022)
Small conservation areas have been created in many countries usually to protect plants and animals, but no priorities are deserved in protecting fungi. The creation of preservation areas is meeting a new problem: there are only small remaining areas, since exploration is destroying large forests. Applying the technique of the transects in three different areas in Brazil (Pampa and Cerrado biomes and Amazonian Forest), diversity and ecological data were collected for Agaricomycetes fungi, mainly order Agaricales, and compared to the fungi already known and their conservation status to understand how fungi are protected indirectly with the creation of small protected areas. The samples were collected in differents permanent protected areas (APP – permanent protected areas) in river margins in southern Brazil (RPAS), Saint Hilaire Forest in the Universidade de Goiás (MSH - ca. 20 ha) in Goiânia/GO and in the Universidade Federal do Amazonas Protected Forest (Manaus/AM - MUFAM), all located in Brazil. In MUFAM, 140 specimens were collected in 2014 and 2018 resulting in 47 species. In MSH 86 specimens were collected in 2019 and 2020 with 31 species identified. In RPAS 278 new species records for the Brazilian Pampa biome were cataloged, 23 new records for the state of Rio Grande do Sul and 4 new registrations for Brazil. This demonstrates the importance of small forest fragments to fungi preservation and maintenance, being efforts in that direction important in future studies of new conservation areas implementation.